Apophysomyces elegans: epidemiology, amplified fragment length polymorphism typing, and in vitro antifungal susceptibility pattern - Chakrabarti, A; Shivaprakash, M R; Curfs-Breuker, I; Baghela, A; Klaassen, C H; Meis, J F (Journal of clinical microbiology, 2010)
Apophysomyces elegans is an emerging pathogen in India. We planned the present study to analyze the clinical pattern of the disease, to perform molecular strain typing, and to determine the in vitro activities of eight antifungal drugs against A. elegans. A total of 16 clinical and two environmental A. elegans isolates were included in the study. The clinical histories of the patients were noted. MICs or minimum effective concentrations (MECs) were determined for antifungal drugs by microdilution testing in accordance with CLSI standard M38-A2 guidelines. Of 16 patients, seven had rhino-cerebral, five had cutaneous, and three had renal zygomycosis. One patient had osteomyelitis. Uncontrolled diabetes was observed in 63% of the patients. Amplified fragment length polymorphism (AFLP) analysis divided the strains into two clearly different clades. The fingerprints of the environmental strains (including the type strain) were clearly different from those of the clinical strains. The MIC50s and MIC90s for amphotericin B, itraconazole, posaconazole, and isavuconazole were 2 and 4, 1 and 2, 0.5 and 1, and 2 and 4 μg/ml, respectively. The strains had high MICs for fluconazole, voriconazole, and echinocandins. The study indicates a possible change in the clinical pattern of zygomycosis due to A. elegans in India. The fungus caused not only cutaneous or subcutaneous infection but also other deep-seated infections, and the disease is commonly associated with uncontrolled diabetes. The AFLP patterns show a clear difference between environmental and clinical strains. Posaconazole is the most active drug against the isolates, followed by itraconazole. The MICs of amphotericin B against A. elegans were higher than those of the other drugs.